2017
DOI: 10.3892/or.2017.5932
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal actions of the phytochemical sulforaphane suppress both AR and AR-V7 in 22Rv1 cells: Advocating a potent pharmaceutical combination against castration-resistant prostate cancer

Abstract: Prostate cancer (PCa) cells expressing full-length androgen receptor (AR-FL) are susceptible to androgen deprivation therapy (ADT). However, outgrowth of castration-resistant prostate cancer (CRPC) can occur due to the expression of constitutively active (ligand-independent) AR splice variants, particularly AR-V7. We previously demonstrated that sulforaphane (SFN), an isothiocyanate phytochemical, can decrease AR-FL levels in the PCa cell lines, LNCaP and C4-2B. Here, we examined the efficacy of SFN in targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 75 publications
3
32
0
Order By: Relevance
“…We recently showed that sulforaphane (SFN) can increase the efficacy of antiandrogens like bicalutamide and enzalutamide by degrading AR in androgen dependent as well as androgen independent PCa cells [ 108 ]. We also showed that SFN can increase the efficacy of enzalutamide in enzalutamide resistant PCa cell line by degrading both AR-FL as well as AR-V7 [ 109 ].…”
Section: Androgen Receptor Signaling and Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that sulforaphane (SFN) can increase the efficacy of antiandrogens like bicalutamide and enzalutamide by degrading AR in androgen dependent as well as androgen independent PCa cells [ 108 ]. We also showed that SFN can increase the efficacy of enzalutamide in enzalutamide resistant PCa cell line by degrading both AR-FL as well as AR-V7 [ 109 ].…”
Section: Androgen Receptor Signaling and Prostate Cancermentioning
confidence: 99%
“…We recently showed that bardoxolone methyl (BM) which is a potent Nrf-2 inducer can increase the efficacy of enzalutamide in an enzalutamide-resistant PCa cell line (CWR22Rv1) by degrading both AR-FL as well as AR-V7 further underscoring the AR suppressive function of Nrf-2 [ 109 ]. This corroborates the fact that AR downregulation and Nrf-2 activation are the major pathways responsible for the anticancer efficacy of phytochemicals like SFN [ 38 , 39 , 40 , 41 , 42 ] and CUR [ 43 , 44 , 45 , 46 , 47 ] in PCa.…”
Section: Interplay Between Nrf-2-antioxidant Nf-κb Inflammatory Amentioning
confidence: 99%
“…Changes in migratory ability of ASCs were measured using Scratch wound assays 62 . Briefly, ASCs were allowed to generate a confluent monolayer in 12-well petri dishes.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot analysis was performed according to our previous published protocols 62 . Briefly, cells were lysed in RIPA buffer from Santa Cruz biosciences (Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Other natural products that have been demonstrated to trigger similar inhibitory effects on the AR axis are sulforaphane [62][63][64][65], epigallocatechin-3-gallate (EGCG) [66,67], ginsenosides [68][69][70][71], silymarin [72], berberine [73], honokiol [74], and celastrol [75].…”
Section: Natural Compounds Modulating the Androgen Receptor Axismentioning
confidence: 99%